The Interspecific Competition Between Larvae of Aedes aegypti and Major African Malaria Vectors in a Semi-Field System in Tanzania - Sperancia Coelestine Lushasi; Yohana A. Mwalugelo; Johnson K. Swai; Arnold S. Mmbando; Letus L. Muyaga; Nhandi K. Nyolobi; Anitha Mutashobya; Augustino T. Mmbaga; Hamisi J. Kunambi; Simoni Twaha; Mwema Felix Mwema; Dickson W. Lwetoijera (Insects)
Interspecific competition between mosquito larvae may affects adult vectorial capacity, potentially reducing disease transmission. It also influences population dynamics, and cannibalistic and predatory behaviors. However, knowledge of interspecific competition between Ae. aegypti and Anopheles species is limited. The study examined interspecific competition between Ae. aegypti larvae and either An.arabiensis, An. gambiae, or An. funestus on individual fitness in semi-field settings. The experiments involved density combinations of 100:100, 200:0, and 0:200 (Ae. aegypti: Anopheles), reared with and without food, in small habitats (8.5 cm height × 15 cm diameter) with 0.5 liters of water and large habitats (15 cm height × 35 cm diameter) with 1 liter of water. The first group received Tetramin® fish food (0.02 g), while the second group was unfed to assess cannibalism and predation. While interspecific competition affected both genera, Anopheles species experienced greater effects, with reduced survival and delayed development, compared to Ae. aegypti. The mean wing lengths of all species were significantly small in small habitats with a mixed population (p < 0.001). The presence of food reduced cannibalism and predation compared to its absence. These interactions have implications for diseases transmission dynamics and can serve as biological indicators to signal the impacts of vector control interventions.